SrTiO3 / BiFeO3 piezoelectric electro-catalytic composite material as well as preparation method and application thereof

By dispersing the SrTiO3 derived from a single layer of Ti3C2 on the surface of BiFeO3, the SrTiO3/BiFeO3 piezoelectric photocatalytic composite material is formed, which solves the problem of low photocatalytic activity of SrTiO3 material and achieves efficient and stable photocatalytic full water-removing reaction performance.

CN119406418AActive Publication Date: 2025-02-11ANHUI UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411548271.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-01
Publication Date
2025-02-11
Estimated Expiration
2044-11-01

AI Technical Summary

Technical Problem

During the photocatalysis process, SrTiO3 material has serious recombination of photogenerated electron-hole pairs, low quantum efficiency and low photocatalytic activity.

Method used

By uniformly dispersing SrTiO3 derived from the monolayer Ti3C2 on the surface of BiFeO3, SrTiO3/BiFeO3 piezoelectric photocatalytic composite material is formed, and SrTiO3 is derivatized in situ by hydrothermal method to improve the specific surface area and photocatalytic activity of the material.

Benefits of technology

The efficient and stable piezoelectric photocatalytic full water-removal reaction performance is achieved without the need for sacrificing agents and additionally adding ionic electron media, thereby improving photocatalytic activity and quantum efficiency.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119406418A_ABST
    Figure CN119406418A_ABST
Patent Text Reader

Abstract

The invention discloses a SrTiO3 / BiFeO3 piezoelectric electro-catalytic composite material and a preparation method and application thereof.The BiFeO3 serves as a substrate of the composite material, and then SrTiO3 derived from single-layer Ti3C2 is evenly dispersed on the surface of the BiFeO3. According to the SrTiO3 / BiFeO3 piezoelectric electro-catalytic composite material, SrTiO3 is derived on the surface of the BiFeO3 in situ through a hydrothermal method to form the SrTiO3 / BiFeO3 piezoelectric electro-catalytic material, and the SrTiO3 / BiFeO3 piezoelectric electro-catalytic composite material can be used for preparing the piezoelectric electro-catalytic material. The synthesis conditions are simple and easy to operate; srTiO3 has excellent light absorption capacity in an ultraviolet region, SrTiO3 derived from single-layer Ti3C2 has a relatively large specific surface area, more active sites are exposed, the photocatalytic activity can be improved, BiFeO3 can form a polarized electric field under the ultrasonic action, a driving force is provided for light-induced charges, photo-induced electron-hole recombination is inhibited, and the photocatalytic activity is improved. The efficient and stable piezoelectric electro-catalysis full water splitting reaction performance of the SrTiO3 / BiFeO3 composite material can be realized under the conditions that a sacrificial agent is not needed and an ionic-state electron medium is additionally added.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of piezoelectric photocatalysis technology, and in particular to a SrTiO 3 / BiFeO 3 Piezoelectric photocatalytic composite material and preparation method and application thereof. Background Art

[0002] As global energy shortages and environmental pollution become increasingly serious, solar energy, as a clean energy source, has attracted much attention due to its abundant resources and environmental friendliness. It can be directly converted into electricity or used to produce other green energy sources, such as hydrogen. As an important part of the future world energy system, hydrogen energy has the advantages of high calorific value, cleanliness, and abundant reserves. Photocatalytic water splitting produces H 2 and O 2 , without relying on sacrificial agents that increase costs and pollute the environment, is considered to be the most efficient and green way to utilize renewable energy.

[0003] The basic principle of photocatalytic reaction is that under light, semiconductor photocatalytic materials absorb photons to generate free electrons and holes. The electron-hole pairs migrate to the surface of the material and undergo oxidation and reduction reactions with the adsorbents on the surface, respectively. However, the electron-hole pairs can easily recombine in the bulk or on the surface during the migration process, and only a small number of carriers can escape the Coulomb force and migrate to the semiconductor surface to participate in the photocatalytic reaction. Therefore, effectively improving the spatial separation of electron-hole pairs is one of the key issues that need to be solved in photocatalytic technology.

[0004] Piezoelectric polarization can be coupled with photoexcitation and semiconductor properties, and the generation, separation, transmission and recombination of carriers can be effectively regulated by polarization electric field. Under the action of external stress, positive and negative polarization charges are formed on the surface of the catalyst, and the positive and negative polarization charges are opposite to the charges of photogenerated electrons and holes. The polarization electric field generated by the directional migration of polarization charges can effectively promote the migration of photogenerated electron-hole pairs in opposite directions, thereby inhibiting the recombination of carriers and greatly improving the separation efficiency of photogenerated carriers.

[0005] Many piezoelectric / ferroelectric materials, such as ZnO, BaTiO 3 , KNbO 3 Lead zirconate titanate (PZT) has been used in the field of piezoelectric photocatalysis, and bismuth multiferrite (BiFeO 3 ) is a prominent p-type semiconductor in solar-driven applications. It has a rhombohedral distorted perovskite structure with an R3c spacer group, has visible light absorption capability (narrow band gap of 2.1 to 2.7 eV), is non-toxic, low-cost, can be spontaneously polarized, and can form a polarized electric field under periodic ultrasound to promote the separation of photogenerated carriers.

[0006] SrTiO 3 It is a highly active, stable, non-toxic, low-cost semiconductor photocatalyst with high thermoelectric power, dielectric constant and metallic conductivity. It has a good response to ultraviolet light, but its photogenerated electron-hole pair recombination phenomenon is serious and the quantum efficiency is low. In addition, SrTiO 3 The material also has disadvantages such as small specific surface area and few exposed catalytic active sites, which will reduce the photocatalytic activity.

[0007] So how to utilize BiFeO 3 The polarization electric field generated by ultrasound promotes the separation of photogenerated electron-hole pairs and the SrTiO 3 The advantages of high activity, high thermoelectric power, dielectric constant and metallic conductivity overcome the disadvantages of SrTiO 3 The material has the disadvantages of serious photogenerated electron-hole pair recombination phenomenon, low quantum efficiency and low photocatalytic activity. The preparation of piezoelectric photocatalytic composite materials with excellent comprehensive performance is the key issue of current research. Summary of the invention

[0008] In view of the shortcomings of the prior art, the present invention aims to provide a SrTiO 3 / BiFeO 3 Piezoelectric photocatalytic composite material and its preparation method and application solve the current SrTiO 3 The material has serious photogenerated electron-hole pair recombination phenomenon, low quantum efficiency and low photocatalytic activity.

[0009] In order to achieve the above object, the present invention adopts the following technical scheme:

[0010] The present invention proposes a SrTiO 3 / BiFeO 3 Piezoelectric photocatalytic composite material, the composite material is BiFeO 3 As the substrate, BiFeO 3 The surface of the 3 C 2 Derived SrTiO 3 .

[0011] Preferably, the BiFeO in the composite material 3 The mass is SrTiO 3 10-50% of the mass.

[0012] The present invention also proposes a SrTiO 3 / BiFeO 3 The preparation method of the piezoelectric photocatalytic composite material comprises the following steps:

[0013] S1. Dissolve KOH in deionized water and mix well to obtain KOH solution. 3 ) 3 ·5H 2 O, Fe(NO 3 ) 3 9H 2 O was added to the KOH solution, stirred to obtain a mixed solution, ultrasonicated, and then the mixed solution was transferred to a reactor and placed in an oven at 180-200°C for 8-10 hours. After the reaction was completed, a precipitate was obtained, cooled, centrifuged, washed, and dried to obtain reddish-brown BiFeO 3 solid;

[0014] S2. Add LiF powder into a beaker containing HCl solution and stir to obtain LiF solution. 3 AlC 2 The powder was added to the LiF solution, and then heated and stirred in an oil bath for etching. After the etching was completed, it was washed with deionized water, the pH value was adjusted to make the solution neutral, and the solution was centrifuged to obtain a sticky precipitate. The precipitate was then dispersed in deionized water, protected by flowing argon gas, and ultrasonicated in an ultrasonic cleaner to obtain a dark green single-layer Ti 3 C 2 Colloid, cryopreserved;

[0015] S3, Sr(OH) 2 8H 2 O powder is dissolved in deionized water to obtain a strontium hydroxide solution, and then the single layer Ti 3 C 2 The colloid is dispersed in a strontium hydroxide solution, and the BiFeO 3 Solid, then transfer the mixed solution to the reactor, and then put it into the homogeneous reactor, the reaction temperature is set to 180-200 ° C, the homogeneous speed is set to 5-20 r / min, after the reaction is completed, cool, and then wash with deionized water, adjust the pH value to make the solution neutral, centrifuge the solution to obtain a precipitate, and then put the solid sample into a muffle furnace for calcination to obtain SrTiO 3 / BiFeO 3 Piezoelectric photocatalytic composites.

[0016] Preferably, in step S1, the stirring time is 30 to 60 minutes; the ultrasonic time is 30 to 60 minutes.

[0017] Preferably, in step S1, the drying temperature is 50-70°C, and the drying time is 10-14h;

[0018] The KOH, Bi(NO 3 )3 ·5H 2 O and Fe(NO 3 ) 3 9H 2 The mass ratio of O is (15~18):(3~6):(2~5).

[0019] Preferably, in step S2, the etching temperature is 50-70° C., and the etching time is 40-48 hours.

[0020] Preferably, the HCl solution is prepared by mixing concentrated hydrochloric acid and water in a volume ratio of 3 to 4:1.

[0021] Preferably, in step S3, the Sr(OH) 2 8H 2 O powder and BiFeO 3 The mass ratio is 8 to 16:1.

[0022] Preferably, in step S3, the rotation speed in the homogeneous reactor is 5 to 20 r / min.

[0023] Preferably, in step S3, the calcination temperature is 500-800°C; the drying temperature is 50-70°C, and the drying time is 10-14 hours.

[0024] The present invention further proposes the SrTiO 3 / BiFeO 3 Application of piezoelectric photocatalytic composite materials to fully split water to produce hydrogen and oxygen under piezoelectric photocatalysis.

[0025] The application specifically comprises the following steps: 3 / BiFeO 3 The piezoelectric photocatalyst was pretreated by photodepositing a certain mass percentage of co-catalyst (0.1wt% Rh, 0.05wt% Cr, 0.05wt% Co), and then ultrasonically dispersed in deionized water. The system was evacuated to remove the air in the system, and argon gas was introduced. The catalytic reaction was carried out under the combined action of visible light and ultrasound, and the hydrogen and oxygen production under piezoelectric photocatalysis was tested by gas chromatography.

[0026] The visible light is provided by a 300W xenon lamp (full spectrum, current intensity is 16A), and the mechanical force is provided by an ultrasonic cleaner (50-120W). To avoid the influence of thermal effects, circulating cooling water is used throughout the process to control the temperature of the entire system at 8°C.

[0027] The present invention uses X-ray powder diffraction and transmission electron microscopy to analyze the SrTiO 3 / BiFeO 3The piezoelectric photocatalytic composites were characterized.

[0028] Compared with the prior art, the present invention has the following beneficial effects:

[0029] The SrTiO provided by the present invention 3 / BiFeO 3 Piezoelectric photocatalytic composites were prepared by hydrothermal method on BiFeO 3 In situ derivatized SrTiO on the surface 3 To form SrTiO 3 / BiFeO 3 Piezoelectric photocatalytic material, its synthesis conditions are simple and easy to operate; SrTiO 3 It has excellent light absorption ability in the ultraviolet region. 3 C 2 Derived SrTiO 3 With a larger specific surface area, BiFeO can expose more active sites and improve the photocatalytic activity. 3 Under the action of ultrasound, a polarization electric field can be formed, which provides a driving force for the photoinduced charge, inhibits the recombination of photogenerated electrons and holes, and helps SrTiO 3 / BiFeO 3 The composite material achieves efficient and stable piezoelectric photocatalytic water splitting reaction performance without the need for sacrificial agents and the addition of ionic electron mediators. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] Figure 1 The SrTiO prepared in Example 1 of the present invention 3 / BiFeO 3 X-ray powder diffraction pattern of the composite material;

[0031] Figure 2 The SrTiO prepared in Example 1 of the present invention 3 / BiFeO 3 Transmission electron microscopy images of the composite material;

[0032] Figure 3 The SrTiO prepared in Example 1 of the present invention 3 / BiFeO 3 UV-visible diffuse reflectance absorption spectrum of the composite material;

[0033] Figure 4 This is a diagram showing the efficiency of the materials prepared in Examples 1-3 of the present invention and Comparative Examples 1-3 in the complete water splitting under piezoelectric photocatalysis;

[0034] Figure 5 The SrTiO prepared in Example 1 of the present invention 3 / BiFeO 3Efficiency diagram of the composite material for total water splitting at different ultrasonic powers. DETAILED DESCRIPTION

[0035] The present invention is further described in detail below through specific preferred embodiments, but the present invention is not limited to the following embodiments.

[0036] It should be noted that, unless otherwise specified, the chemical reagents involved in the present invention were purchased through commercial channels.

[0037] Example 1

[0038] A SrTiO 3 / BiFeO 3 The preparation method of the piezoelectric photocatalytic composite material comprises the following steps:

[0039] (1) Dissolve 16.83 g of KOH in 30 mL of deionized water, ultrasonicate to obtain a KOH solution, and then add 4.85 g of Bi(NO 3 ) 3 ·5H 2 O and 3.32 g of Fe(NO 3 ) 3 9H 2 O were added to the above KOH solution, stirred for 50 min to obtain a mixed solution, then ultrasonicated for 30 min, and then the mixed solution was transferred to a reactor with a polytetrafluoroethylene liner and placed in an oven at 200 ° C for 9 h. After the reaction was completed, a precipitate was obtained, cooled, centrifuged, washed, and dried to obtain a reddish brown BiFeO 3 solid;

[0040] (2) 2.0 g of LiF powder was slowly added into a polytetrafluoroethylene beaker containing 20 mL of HCl solution (concentration: 9 M) and stirred at room temperature for 1 h to obtain a LiF solution. 2.0 g of Ti 3 AlC 2 The powder was slowly added to the LiF solution, and then heated to 60°C in an oil bath and stirred for etching for 46 hours. After the etching was completed, it was washed with deionized water, and the pH value was adjusted to 7 to make the solution neutral. The solution was centrifuged to obtain a sticky precipitate, which was then dispersed in deionized water, protected by flowing argon gas, and ultrasonicated in an ultrasonic cleaner to obtain a dark green single-layer Ti 3 C 2 Colloid, cryopreserved;

[0041] (3) Weigh 4 g of Sr(OH) 2 8H 2 O powder was slowly added into a beaker containing 40 mL of deionized water and stirred evenly at room temperature. 0.76 g of single-layer Ti3 C 2 colloid, and then add 0.25g of BiFeO 3 The powder was stirred evenly and then the solution was transferred to a polytetrafluoroethylene reactor and reacted in a homogeneous phase at 180°C for 2 hours. The speed in the homogeneous reactor was 5 r / min. After the hydrothermal reaction, the reaction solution was centrifuged and washed with deionized water until neutral. The washed product was dried in a vacuum drying oven at 60°C for 24 hours. Finally, the dried sample was calcined in a muffle furnace at 600°C for 1 hour to obtain SrTiO 3 / BiFeO 3 Piezoelectric photocatalytic composites.

[0042] Example 2

[0043] A SrTiO 3 / BiFeO 3 The preparation method of the piezoelectric photocatalytic composite material comprises the following steps:

[0044] (1) Dissolve 16.83 g of KOH in 30 mL of deionized water, ultrasonicate to obtain a KOH solution, and then add 4.85 g of Bi(NO 3 ) 3 ·5H 2 O and 3.32 g of Fe(NO 3 ) 3 9H 2 O were added to the above KOH solution, stirred for 50 min to obtain a mixed solution, then ultrasonicated for 30 min, and then the mixed solution was transferred to a reactor with a polytetrafluoroethylene liner and placed in an oven at 200 ° C for 9 h. After the reaction was completed, a precipitate was obtained, cooled, centrifuged, washed, and dried to obtain a reddish brown BiFeO 3 solid;

[0045] (2) 2.0 g of LiF powder was slowly added into a polytetrafluoroethylene beaker containing 20 mL of HCl solution (concentration: 9 M) and stirred at room temperature for 1 h to obtain a LiF solution. 2.0 g of Ti 3 AlC 2 The powder was slowly added to the LiF solution, and then heated to 60°C in an oil bath and stirred for etching for 46 hours. After the etching was completed, it was washed with deionized water, and the pH value was adjusted to 7 to make the solution neutral. The solution was centrifuged to obtain a sticky precipitate, which was then dispersed in deionized water, protected by flowing argon gas, and ultrasonicated in an ultrasonic cleaner to obtain a dark green single-layer Ti 3 C 2 Colloid, cryopreserved;

[0046] (3) Weigh 4 g of Sr(OH) 28H 2 O powder was slowly added into a beaker containing 40 mL of deionized water and stirred evenly at room temperature. 0.76 g of single-layer Ti 3 C 2 colloid, and then add 0.5g BiFeO 3 The powder was stirred evenly and then the solution was transferred to a polytetrafluoroethylene reactor and reacted in a homogeneous phase at 180°C for 2 hours. The speed in the homogeneous reactor was 5 r / min. After the hydrothermal reaction, the reaction solution was centrifuged and washed with deionized water until neutral. The washed product was dried in a vacuum drying oven at 60°C for 24 hours. Finally, the dried sample was calcined in a muffle furnace at 600°C for 1 hour to obtain SrTiO 3 / BiFeO 3 Piezoelectric photocatalytic composites.

[0047] Example 3

[0048] A SrTiO 3 / BiFeO 3 The preparation method of the piezoelectric photocatalytic composite material comprises the following steps:

[0049] (1) Dissolve 16.83 g of KOH in 30 mL of deionized water, ultrasonicate to obtain a KOH solution, and then add 4.85 g of Bi(NO 3 ) 3 ·5H 2 O and 3.32 g of Fe(NO 3 ) 3 9H 2 O were added to the above KOH solution, stirred for 50 min to obtain a mixed solution, then ultrasonicated for 30 min, and then the mixed solution was transferred to a reactor with a polytetrafluoroethylene liner and placed in an oven at 200 ° C for 9 h. After the reaction was completed, a precipitate was obtained, cooled, centrifuged, washed, and dried to obtain a reddish brown BiFeO 3 solid;

[0050] (2) 2.0 g of LiF powder was slowly added into a polytetrafluoroethylene beaker containing 20 mL of HCl solution (concentration: 9 M) and stirred at room temperature for 1 h to obtain a LiF solution. 2.0 g of Ti 3 AlC 2 The powder was slowly added to the LiF solution, and then heated to 60°C in an oil bath and stirred for etching for 46 hours. After the etching was completed, it was washed with deionized water, and the pH value was adjusted to 7 to make the solution neutral. The solution was centrifuged to obtain a sticky precipitate, which was then dispersed in deionized water, protected by flowing argon gas, and ultrasonicated in an ultrasonic cleaner to obtain a dark green single-layer Ti 3 C 2Colloid, cryopreserved;

[0051] (3) Weigh 4 g of Sr(OH) 2 8H 2 O powder was slowly added into a beaker containing 40 mL of deionized water and stirred evenly at room temperature. 0.76 g of single-layer Ti 3 C 2 colloid, and then add 0.25g of BiFeO 3 The powder was stirred evenly and then the solution was transferred to a polytetrafluoroethylene reactor and reacted in a homogeneous phase at 180°C for 2 hours. The speed in the homogeneous reactor was 5 r / min. After the hydrothermal reaction, the reaction solution was centrifuged and washed with deionized water until neutral. The washed product was dried in a vacuum drying oven at 60°C for 24 hours. Finally, the dried sample was calcined in a muffle furnace at 800°C for 1 hour to obtain SrTiO 3 / BiFeO 3 Piezoelectric photocatalytic composites.

[0052] Example 4

[0053] A SrTiO 3 / BiFeO 3 The preparation method of the piezoelectric photocatalytic composite material comprises the following steps:

[0054] (1) Dissolve 16.83 g of KOH in 30 mL of deionized water, ultrasonicate to obtain a KOH solution, and then add 4.85 g of Bi(NO 3 ) 3 ·5H 2 O and 3.32 g of Fe(NO 3 ) 3 9H 2 O were added to the above KOH solution, stirred for 50 min to obtain a mixed solution, then ultrasonicated for 30 min, and then the mixed solution was transferred to a reactor with a polytetrafluoroethylene liner and placed in an oven at 200 ° C for 9 h. After the reaction was completed, a precipitate was obtained, cooled, centrifuged, washed, and dried to obtain a reddish brown BiFeO 3 solid;

[0055] (2) 2.0 g of LiF powder was slowly added into a polytetrafluoroethylene beaker containing 20 mL of HCl solution (concentration: 9 M) and stirred at room temperature for 1 h to obtain a LiF solution. 2.0 g of Ti 3 AlC 2The powder was slowly added to the LiF solution, and then heated to 50°C in an oil bath and stirred for etching for 46 hours. After the etching was completed, it was washed with deionized water, and the pH value was adjusted to 7 to make the solution neutral. The solution was centrifuged to obtain a sticky precipitate, which was then dispersed in deionized water, protected by flowing argon gas, and ultrasonicated in an ultrasonic cleaner to obtain a dark green single-layer Ti 3 C 2 Colloid, cryopreserved;

[0056] (3) Weigh 4 g of Sr(OH) 2 8H 2 O powder was slowly added into a beaker containing 40 mL of deionized water and stirred evenly at room temperature. 0.76 g of single-layer Ti 3 C 2 colloid, and then add 0.5g BiFeO 3 The powder was stirred evenly and then the solution was transferred to a polytetrafluoroethylene reactor and reacted in a homogeneous phase at 180°C for 2 hours. The speed in the homogeneous reactor was 10 r / min. After the hydrothermal reaction, the reaction solution was centrifuged and washed with deionized water until neutral. The washed product was dried in a vacuum drying oven at 60°C for 24 hours. Finally, the dried sample was calcined in a muffle furnace at 800°C for 1 hour to obtain SrTiO 3 / BiFeO 3 Piezoelectric photocatalytic composites.

[0057] Example 5

[0058] A SrTiO 3 / BiFeO 3 The preparation method of the piezoelectric photocatalytic composite material comprises the following steps:

[0059] (1) Dissolve 16.83 g of KOH in 30 mL of deionized water, ultrasonicate to obtain a KOH solution, and then add 4.85 g of Bi(NO 3 ) 3 ·5H 2 O and 3.32 g of Fe(NO 3 ) 3 9H 2 O were added to the above KOH solution, stirred for 50 min to obtain a mixed solution, then ultrasonicated for 30 min, and then the mixed solution was transferred to a reactor with a polytetrafluoroethylene liner and placed in an oven at 200 ° C for 9 h. After the reaction was completed, a precipitate was obtained, cooled, centrifuged, washed, and dried to obtain a reddish brown BiFeO 3 solid;

[0060] (2) 2.0 g of LiF powder was slowly added into a polytetrafluoroethylene beaker containing 20 mL of HCl solution (concentration: 9 M) and stirred at room temperature for 1 h to obtain a LiF solution. 2.0 g of Ti 3 AlC 2 The powder was slowly added to the LiF solution, and then heated to 70°C in an oil bath and stirred for etching for 46 hours. After the etching was completed, it was washed with deionized water, and the pH value was adjusted to 7 to make the solution neutral. The solution was centrifuged to obtain a sticky precipitate, which was then dispersed in deionized water, protected by flowing argon gas, and ultrasonicated in an ultrasonic cleaner to obtain a dark green single-layer Ti 3 C 2 Colloid, cryopreserved;

[0061] (3) Weigh 4 g of Sr(OH) 2 8H 2 O powder was slowly added into a beaker containing 40 mL of deionized water and stirred evenly at room temperature. 0.76 g of single-layer Ti 3 C 2 colloid, and then add 0.25g of BiFeO 3 The powder was stirred evenly and then the solution was transferred to a polytetrafluoroethylene reactor and reacted in a homogeneous phase at 180°C for 2 hours. The speed in the homogeneous reactor was 10 r / min. After the hydrothermal reaction, the reaction solution was centrifuged and washed with deionized water until neutral. The washed product was dried in a vacuum drying oven at 60°C for 24 hours. Finally, the dried sample was calcined in a muffle furnace at 600°C for 1 hour to obtain SrTiO 3 / BiFeO 3 Piezoelectric photocatalytic composites.

[0062] Comparative Example 1

[0063] A method for synthesizing a piezoelectric photocatalyst comprises the following steps:

[0064] 16.83 g of KOH was dissolved in 30 mL of deionized water, and KOH solution was obtained by ultrasonication. Then 4.85 g of Bi(NO 3 ) 3 ·5H 2 O and 3.32 g of Fe(NO 3 ) 3 9H 2 O were added to the above KOH solution, stirred for 50 min to obtain a mixed solution, then ultrasonicated for 30 min, and then the mixed solution was transferred to a reactor with a polytetrafluoroethylene liner and placed in an oven at 200 ° C for 9 h. After the reaction was completed, a precipitate was obtained, cooled, centrifuged, washed, and dried to obtain a reddish brown BiFeO 3 solid.

[0065] Comparative Example 2

[0066] A method for synthesizing a piezoelectric photocatalyst comprises the following steps:

[0067] (1) 2.0 g of LiF powder was slowly added into a polytetrafluoroethylene beaker containing 20 mL of HCl solution (9 M concentration) and stirred at room temperature for 1 h to obtain a LiF solution. 2.0 g of Ti 3 AlC 2 The powder was slowly added to the LiF solution, and then heated and stirred in an oil bath for 46 hours. After the etching was completed, it was washed with deionized water, and the pH value was adjusted to 7 to make the solution neutral. The solution was centrifuged to obtain a sticky precipitate, which was then dispersed in deionized water, protected by flowing argon gas, and ultrasonicated in an ultrasonic cleaner to obtain a dark green single-layer Ti 3 C 2 Colloid, cryopreserved;

[0068] (2) Weigh 0.5 g of Sr(OH) 2 8H 2 O powder was slowly added into a beaker containing 40 mL of deionized water, stirred evenly at room temperature, and 0.1 g of a single layer of Ti 3 C 2 The colloid was stirred evenly and then the solution was transferred to a polytetrafluoroethylene reactor and reacted in a homogeneous phase at 180°C for 2h, wherein the speed in the homogeneous reactor was 5r / min. After the hydrothermal reaction was completed, the reaction solution was centrifuged and washed with deionized water until neutral, and then the washed product was dried in a vacuum drying oven at 60°C for 24h, and finally the dried sample was calcined in a muffle furnace at 600°C for 1h to obtain a single-layer Ti 3 C 2 SrTiO as Ti source 3 solid.

[0069] Comparative Example 3

[0070] A method for synthesizing a piezoelectric photocatalyst comprises the following steps:

[0071] Weigh 2.5g of commercial SrTiO 3 The powder was put into an agate mortar and 0.25 g of BiFeO 3 The powder was wet-grinded for 30 min to fully mix and obtain SrTiO 3 / BiFeO 3 Composite materials.

[0072] Application Examples

[0073] The catalysts prepared in Examples 1 to 3 of the present invention and Comparative Examples 1 to 3 were used for photocatalytic water splitting. Before the performance evaluation, all catalysts were pre-treated by photodepositing a certain mass percentage of promoters (0.1 wt % Rh, 0.05 wt % Cr, 0.05 wt % Co). During the performance evaluation, 50 mg of SrTiO 3 Solid, BiFeO 3 Solid and SrTiO 3 / BiFeO 3 The solid was placed in a photocatalytic reactor with 50 mL of deionized water, connected to a photocatalytic performance evaluation device, the system was evacuated to remove the air in the system before the photocatalytic reaction, and the piezoelectric-photocatalytic water splitting test was carried out under the condition of a 300W xenon lamp (full spectrum). The product was analyzed by an online gas chromatograph equipped with a TCD detector.

[0074] The piezoelectric photocatalytic test is similar to the photocatalytic test process. The main difference is that during the piezoelectric photocatalytic test, the reactor is placed in an ultrasonic cleaner (50-120W), which applies a mechanical stress during the reaction.

[0075] Test results and analysis

[0076] The SrTiO prepared in Example 1 was characterized by X-ray powder diffraction (XRD). 3 / BiFeO 3 The crystal structure of the composite material was characterized and the Figure 1 ; SrTiO prepared in Example 1 was observed by transmission electron microscopy 3 / BiFeO 3 The morphology of the composite material was obtained Figure 2 ; Observation of SrTiO by UV diffuse reflectance absorption spectroscopy 3 / BiFeO 3 The absorption range of composite materials to light is obtained Figure 3 By comparing the efficiency of the composite materials prepared in Examples 1-3 and Comparative Examples 1-3 in the complete water splitting under piezoelectric photocatalysis, the following results are obtained: Figure 4 ; By statistically analyzing the SrTiO prepared in Example 1 3 / BiFeO 3 The efficiency of water decomposition of the composite material under different ultrasonic powers is obtained. Figure 5 .

[0077] Figure 1 The SrTiO prepared in Example 1 is shown in 3 / BiFeO 3 XRD spectrum of the composite material. Comparing the XRD PDF cards of bismuth ferrite and strontium titanate, it was found that SrTiO 3 / BiFeO3 Composite materials, from Figure 1 It can be seen that the introduction of bismuth ferrite does not change the crystal structure of strontium titanate, and there are no extra peaks in the XRD spectrum, proving that SrTiO 3 / BiFeO 3 The composite material has excellent purity and crystallinity.

[0078] Figure 2 The SrTiO prepared in Example 1 3 / BiFeO 3 SEM image of the composite material. Bismuth ferrite nanomaterial is a cubic block material consisting of a single layer of Ti 3 C 2 The derived strontium titanate is an irregular cubic shape. Figure 2 It can be seen that many small particles are attached to the surface of bismuth ferrite nanomaterials, and strontium titanate is evenly dispersed on the surface of bismuth ferrite.

[0079] Figure 3 The SrTiO prepared in Example 1 3 / BiFeO 3 UV-vis-DRS diffuse reflectance spectrum of the composite material shows that SrTiO 3 / BiFeO 3 The composite material has good light absorption in the ultraviolet region.

[0080] Figure 4 The efficiency diagram of the composite materials prepared in Examples 1-3 and Comparative Examples 1-3 under piezoelectric photocatalysis is shown in Figure 2. Compared with Comparative Examples 1-3, the overall water splitting performance of Examples 1 to 3 is better, indicating that SrTiO 3 / BiFeO 3 The photocatalytic performance of the composite material is higher than that of single SrTiO 3 Materials and BiFeO 3 materials, also higher than SrTiO 3 and BiFeO 3 The catalyst obtained by physical mixing. Compared with Example 1, Example 2 has better water splitting performance, indicating that BiFeO 3 The higher the content, the stronger the piezoelectric effect, and the more it can promote the migration of carriers.

[0081] Figure 5 The SrTiO prepared in Example 1 3 / BiFeO 3 The efficiency of the composite material in water splitting under different ultrasonic powers. Figure 5It can be seen that as the ultrasonic power increases, the amount of hydrogen and oxygen released from the composite material also increases. This shows that as the ultrasonic power increases, the piezoelectric effect also increases, which will further promote the separation of carriers.

[0082] Finally, it should be noted that the above embodiments do not limit the present invention in any form. For those skilled in the art, some modifications and improvements can be made to the present invention. Therefore, any modification or improvement made without departing from the spirit of the present invention belongs to the scope of protection claimed in the present invention.

Claims

1. A SrTiO3 / BiFeO3 piezoelectric photocatalytic composite material, characterized in that: The composite material takes BiFeO3 as a substrate, and SrTiO3 is in-situ derived on the surface of BiFeO3.

2. The SrTiO3 / BiFeO3 piezoelectric photocatalytic composite material according to claim 1, characterized in that: The mass of BiFeO3 in the composite material is 10-50% of the mass of SrTiO3.

3. A method for preparing a SrTiO3 / BiFeO3 piezoelectric photocatalytic composite material, characterized in that: The following steps are involved: S1. Add Bi(NO3)3·5H2O and Fe(NO3)3·9H2O to KOH solution, stir to obtain a mixed solution, ultrasonicate, then transfer the mixed solution to a reactor, place it in an oven at 180-200°C for 8-10 hours, and after the reaction is completed, obtain a precipitate, cool, centrifuge, wash, and dry to obtain a reddish-brown BiFeO3 solid; S2, weigh Ti3AlC2 powder, add it to LiF solution, heat and stir to etch, after etching is completed, wash, centrifuge to obtain a precipitate, then disperse the precipitate in water, protect it with flowing argon gas, and then perform ultrasound to obtain a dark green single-layer Ti3C2 colloid, which is frozen for storage; S3. Dissolve Sr(OH)2·8H2O powder in deionized water to obtain a strontium hydroxide solution, disperse the monolayer Ti3C2 colloid in the strontium hydroxide solution, add the BiFeO3 solid, transfer the mixed solution to a reactor, and then put it into a homogeneous reactor. Set the reaction temperature to 180-200°C and the homogeneous speed to 5-20 r / min. After the reaction is completed, cool, wash, and centrifuge to obtain a precipitate. Then calcine the precipitate to obtain a SrTiO3 / BiFeO3 piezoelectric photocatalytic composite material.

4. The method for preparing the SrTiO3 / BiFeO3 piezoelectric photocatalytic composite material according to claim 3, characterized in that: In step S1, the stirring time is 30 to 60 minutes; the ultrasonic time is 30 to 60 minutes.

5. The method for preparing the SrTiO3 / BiFeO3 piezoelectric photocatalytic composite material according to claim 3, characterized in that: In step S1, the mass ratio of KOH, Bi(NO3)3·5H2O and Fe(NO3)3·9H2O is (15-18):(3-6):(2-5).

6. The method for preparing the SrTiO3 / BiFeO3 piezoelectric photocatalytic composite material according to claim 3, characterized in that: In step S2, the etching temperature is 50-70° C., and the etching time is 40-48 hours.

7. The method for preparing the SrTiO3 / BiFeO3 piezoelectric photocatalytic composite material according to claim 3, characterized in that: In step S3, the mass ratio of the Sr(OH)2·8H2O powder to BiFeO3 is 8 to 16:

1.

8. The method for preparing the SrTiO3 / BiFeO3 piezoelectric photocatalytic composite material according to claim 3, characterized in that: In step S3, the rotation speed in the homogeneous reactor is 5 to 20 r / min.

9. The method for preparing the SrTiO3 / BiFeO3 piezoelectric photocatalytic composite material according to claim 3, characterized in that: In step S3, the calcination temperature is 500-800°C.

10. Use of the SrTiO3 / BiFeO3 piezoelectric photocatalytic composite material according to claim 1 or 2 for fully splitting water to produce hydrogen and oxygen under piezoelectric photocatalysis.

Citation Information

Patent Citations

  • MXene-derived SrTiO3-based photocatalyst and application thereof

    CN115582111A

  • Mxene layers as substrates for growth of highly oriented perovskite thin films

    US20200240000A1